POTENSI EKSTRAK KARAMUNTING (MELASTOMA MALABATHRICUM L.) SEBAGAI INSEKTISIDA NABATI UNTUK MENGENDALIKAN ULAT GRAYAK (SPODOPTERA LITURA F.) - Kartina, Kartina; Shulkipli, Shulkipli; Mardhiana, Mardhiana; Egra, Saat (Universitas Medan Area, 2019)
Spodoptera litura F. is one of the important pests in Horticulture commodities which can cause damage 80% and up to 100%. Karamunting (Melastome malabathricum) is a wild plant that grows in Tarakan City. This plant is known to contain secondary metabolites which are thought to have the potential to control pests. This study aims to determine the potential of Karamunting extract as a botanical insecticide material to control armyworms. This study uses a completely randomized design (CRD) method with 1 treatment factor, namely the concentration of Karamunting leaf extract. Potential extracts as botanical insecticides were tested by dye method using 4 concentrations, namely 0 (control); 500; 1000; 2000; 4000; and 8000 ppm. The results showed that Karamunting leaf extract was able to control armyworm pests. Giving extracts of 8000 ppm (P5) in feed caused the highest decrease in eating activity up to 41,2%, larval mortality up to 85%, and the highest mortality rate after 7 days of observation. Decreased feeding activity and larval mortality were thought to be influenced by the presence of phenol compounds, fatty acids, terpenoids, sterols and alkaloids identified in the extract. Thus, Karamunting leaf extract has the potential to be developed as an active ingredient in botanical insecticides to control armyworm.